Defect-tolerant electron and defect-sensitive phonon transport in quasi-2D conjugated coordination polymers - Un, Hio-Ieng; Iwanowski, Kamil; Ferrer Orri, Jordi; Jacobs, Ian E.; Fukui, Naoya; Cornil, David; Beljonne, David; Simoncelli, Michele; Nishihara, Hiroshi; Sirringhaus, Henning (Nature communications, 2025)
Thermoelectric materials, enabling direct waste-heat to electricity conversion, need to be highly electrically conducting while simultaneously thermally insulating. This is fundamentally challenging since electrical and thermal conduction usually change in tandem. In quasi-two-dimensional conjugated coordination polymer films we discover an advantageous thermoelectric transport regime, in which charge transport is defect-tolerant but heat propagation is defect-sensitive; it imparts the ideal mix of antithetical properties—temperature-activated, exceptionally low lattice thermal conductivities of 0.2 W m −1 K −1 below Kittel’s limit originating from small-amplitude, quasi-harmonic lattice dynamics with disorder-limited lifetimes and vibrational scattering length on the order of interatomic spacing, and high electrical conductivities up to 2000 S cm −1 with metallic temperature dependence, notably in poorly crystalline structures with paracrystallinity >10%. These materials offer attractive properties, such as ease of processing and defect tolerance, for applications, that require fast charge, but slow heat transport. Thermoelectric materials are required to be electrically conducting while thermally insulating, which can be challenging to achieve. Here, the authors report a thermoelectric transport regime with defect tolerant charge transport but defect intolerant heat propagation in two-dimensional coordination polymer films.